A companion to Faulkner studies - Peek, Charles A.; Hamblin, Robert W. (Greenwood Press, 2004)
Faulkner scholarship is one of the largest critical enterprises currently at work. Because of its size and scope, accessing that scholarship has become difficult for scholars, students, and general readers alike. This reference includes chapters on individual approaches to Faulkner studies, including archetypal, historical, biographical, feminist, and psychological criticism, among others. Each chapter is written by an expert contributor and surveys the contributions of that approach to Faulkner scholarship. The volume concludes with a selected, general bibliography and glossary of critical te.